Methodology for Single-Cell Genetic Analysis of Planktonic Foraminifera for Studies of Protist Diversity and Evolution - Weiner, Agnes K. M.; Morard, Raphael; Weinkauf, Manuel F. G.; Darling, Kate F.; André, Aurore; Quillévéré, Frédéric; Ujiie, Yurika; Douady, Christophe J.; de Vargas, Colomban; Kucera, Michal (Frontiers in Marine Science, 2016)
Single-cell genetic analysis is an essential method to investigate the biodiversity and evolutionary ecology of marine protists. In protist groups that do not reproduce under laboratory conditions, this approach provides the only means to directly associate molecular sequences with cell morphology. The resulting unambiguous taxonomic identification of the DNA sequences is a prerequisite for barcoding and analyses of environmental metagenomic data. Extensive single-cell genetic studies have been carried out on planktonic foraminifera over the past 20 years to elucidate their phylogeny, cryptic diversity, biogeography and the relationship between genetic and morphological variability. In the course of these investigations, it has become evident that genetic analysis at the individual specimen level is confronted by innumerable challenges ranging from the negligible amount of DNA present in the single cell to the substantial amount of DNA contamination introduced by endosymbionts or food particles. Consequently, a range of methods has been developed and applied throughout the years for the genetic analysis of planktonic foraminifera in order to enhance DNA amplification success rates. Yet, the description of these methods in the literature rarely occurred with equivalent levels of detail and the different approaches have never been compared in terms of their efficiency and reproducibility. Here, aiming at a standardization of methods, we provide a comprehensive review of all methods that have been employed for the single-cell genetic analysis of planktonic foraminifera. We compile data on success rates of DNA amplification and use these to evaluate the effects of key parameters associated with the methods of sample collection, storage and extraction of single-cell DNA. We show that the chosen methods influence the success rates of single-cell genetic studies, but the differences between them are not sufficient to hinder comparisons between studies carried out by different methods. The review thus not only provides a comprehensive reference with guidelines for future genetic studies on foraminifera, but it also establishes an important benchmark for investigations using existing single-cell datasets. The methods are widely applicable and the review may help to establish similar standard principles for their utilization in other protist groups.